Karma Dalam Agama Buddha: Systematic Literature Review - Angela, Shelfia; Partono Nyanasuryanadi; Kabri (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya Wonogiri, 2024)
The concept of Kamma (Karma) embodies the principle of causality, where every action has a corresponding consequence. Buddhism considers the theory of Kamma as a basic principle in its teachings. This research uses the System Literature Review (SLR) method to analyze relevant previous research regarding the concept of karma in Buddhism. Meta-synthesis was carried out to answer the research question, namely what is the concept of karma in Buddhism. The aim of this SLR research is to gain a deeper understanding of Kamma in Buddhism; increasing understanding through literacy studies from ten selected studies; thoroughly examine research and intensity of discussion; and provides evidence that the concept of karma exists in Buddhism. The systematic review carried out was using the PRISMA method, evaluating articles published between 2019 and 2023. Research articles related to karma were obtained by searching using the keyword